2018
DOI: 10.1002/smll.201704379
|View full text |Cite|
|
Sign up to set email alerts
|

Uniform Luminous Perovskite Nanofibers with Color‐Tunability and Improved Stability Prepared by One‐Step Core/Shell Electrospinning

Abstract: A one-step core/shell electrospinning technique is exploited to fabricate uniform luminous perovskite-based nanofibers, wherein the perovskite and the polymer are respectively employed in the core and the outer shell. Such a coaxial electrospinning technique enables the in situ formation of perovskite nanocrystals, exempting the needs of presynthesis of perovskite quantum dots or post-treatments. It is demonstrated that not only the luminous electrospun nanofibers can possess color-tunability by simply tuning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
85
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 41 publications
1
85
0
2
Order By: Relevance
“…Such pleasing features have empowered this evolving class of materials to be applied in the light-emitting diodes, light-emitting transistors, and photomemories in addition to the light-harvesting-related applications. [14] Reports from several authors have indicated the following interesting achievements; drastic increase in the PCE from 3.8% in 2009, [15] to 23.7% in a period of 10 years, a remarkable improvement in stability from a few hours of operation to a maximum life time of 1 year [16] and beyond, broadened range of materials including flexible and cheap substances and a notable reduction in production costs due to the ease of assembling methods. [17] However, due to the numerous advantages associated with the fiber geometry such as the light weight, increased flexibility, and the ease of conversion into other structures such as fabrics, together with an increasing demand for textile-based energy-harvesting devices, developed with the intent of powering in body, on body, near body, and other wearable electronics, [18][19][20] the research in the domain of fiber-shaped solar cells is slowly following the footsteps of their 2D counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Such pleasing features have empowered this evolving class of materials to be applied in the light-emitting diodes, light-emitting transistors, and photomemories in addition to the light-harvesting-related applications. [14] Reports from several authors have indicated the following interesting achievements; drastic increase in the PCE from 3.8% in 2009, [15] to 23.7% in a period of 10 years, a remarkable improvement in stability from a few hours of operation to a maximum life time of 1 year [16] and beyond, broadened range of materials including flexible and cheap substances and a notable reduction in production costs due to the ease of assembling methods. [17] However, due to the numerous advantages associated with the fiber geometry such as the light weight, increased flexibility, and the ease of conversion into other structures such as fabrics, together with an increasing demand for textile-based energy-harvesting devices, developed with the intent of powering in body, on body, near body, and other wearable electronics, [18][19][20] the research in the domain of fiber-shaped solar cells is slowly following the footsteps of their 2D counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Realization of practical LHP NC emitters is critically dependent upon improving their structural, thermodynamical, and optical stability under ambient conditions, which remains the foremost challenge for such nanomaterials (Huang et al, 2017; Kovalenko et al, 2017; Akkerman et al, 2018; Zhao et al, 2018). Encapsulation of perovskite NCs into macro- or nanoscale polymeric structures has been recently demonstrated (Huang et al, 2016; Raja et al, 2016; Wang et al, 2016, 2017; Hou et al, 2017; Lu et al, 2017; Ma et al, 2017; Murphy et al, 2017; Demkiv et al, 2018; Liao et al, 2018; Lin et al, 2018; Sygletou et al, 2018; Tsai et al, 2018; Wong et al, 2018; Xin et al, 2018; Yang M. et al, 2018; Yang S. et al, 2018; Zhang et al, 2018; Zhu et al, 2018) as simple and low-cost methodologies to preserve the LHP NC chemical integrity by suppressing water and oxygen transmission, improving the thermal stability, and reducing structural modifications, to which LHP NCs are highly susceptible, such as ligand desorption and nanocrystal sintering. Furthermore, integration of the NCs into polymers provides a method to improve their solid-state processability into films, microspheres, fibers, or more complex composites while offering new functionalities such as polarizing PL (Raja et al, 2016; Lu et al, 2017), light detection (Wang et al, 2016), biological labeling and sensing (Wang et al, 2017; Zhu et al, 2018) or device applications such as light emitting diodes (Huang et al, 2016; Liao et al, 2018; Lin et al, 2018; Tsai et al, 2018; Xin et al, 2018; Yang M. et al, 2018; Zhang et al, 2018; Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning allows for a simple, cost-effective and industrially scalable fabrication of long and continuous polymer fibers (Persano et al, 2013; Yu et al, 2017; Savva and Krasia-Christoforou, 2018), enabling the incorporation of a variety of inorganic nanoparticles and thus generating functional nanocomposites (Chronakis, 2015). Fiber composite emitters appear particularly attractive for optoelectronics bearing unique properties such as tolerance to extremely small bending radii and large tensile strains while preserving the structural integrity and bright emission of the perovskite NCs (Wang et al, 2016, 2017; Murphy et al, 2017; Liao et al, 2018; Lin et al, 2018; Tsai et al, 2018; Yang M. et al, 2018). In particular, enhanced water/optical (Wang et al, 2016, 2017; Murphy et al, 2017; Liao et al, 2018; Lin et al, 2018; Tsai et al, 2018; Yang M. et al, 2018) and thermal (Liao et al, 2018) stabilities have been demonstrated upon nanocrystal encapsulation into polymer fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the preparation of composite nanomaterials, multiple preparation methods have been used, such as the absorption method, hydrothermal method, solvothermal method, and sol-gel method. In particular, the one-step method is a simple and fast synthesis method [12]. As a doping antimicrobial agent, silver has been demonstrated to have excellent antimicrobial activity and very insignificant changes in the mechanical properties of the material [13].…”
Section: Introductionmentioning
confidence: 99%